PENJATUHAN SANKSI DALAM PENYELESAIAN PERSELISIHAN HUBUNGAN INDUSTRIAL - I Gusti Ngurah Adnyana (Jurnal Cakrawala Hukum, 2017)
Manpower law was mixed. It meant that it consisted of civil law aspect, and public law aspect, so the lawbreaker would get civil sanction, criminal sanction, and administrative one. The solution of industrial relationdisagreementas regulated in regulation no 2 year 2004 did not regulate the solution of industrial relationdisagreement which happened because of violation to manpower law which was pubic. The stipulation inregulation no 2 year 2004 merely regulated disagreement solution as what written in civil law, either out ofcourt or through industrial relation court by submitting suit